Composite slurry and its preparation method and application

By using composite slurry of specific proportions and particle sizes for repair, the problem of poor binding force of coated carbon ceramic brake disc repair agent is solved, and efficient and economical repair effect is achieved, and the density and binding force of the repair layer are improved.

CN119350941BActive Publication Date: 2025-03-18HUNAN KINGBO CARBON CARBON COMPOSITES CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411898035.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The repair agent of the existing coated carbon ceramic brake disc has poor bonding force with the brake disc body, resulting in unsatisfactory repair effect and high repair cost.

Method used

A composite slurry is provided, and its components include a specific proportion of silicon particles, silicon carbide particles, graphite particles and resin solution. By controlling the particle size and proportion of each particle, the bonding force of the repair layer and the coating carbon ceramic brake disc has a good bonding force, and the repair layer has a high density.

Benefits of technology

The good bonding and consistency between the repair layer and the coated carbon ceramic brake disc is achieved, the compactness of the repair layer is improved, the repair process is simplified, the repair cost is reduced, and the repair pass rate and service life is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to a composite slurry and its preparation method and application. The composite slurry, whose components include 5% to 10% silicon particles, 55% to 65% silicon carbide particles, 5% to 10% graphite particles and 25% to 35% resin solution, the D50 particle size of the silicon particles is 38μm to 80μm, the D50 particle size of the silicon particles is smaller than the D50 particle size of the silicon carbide particles, and the D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon carbide particles. The components of the composite slurry include a specific proportion of graphite particles, silicon particles, graphite particles and resin solution. By controlling the particle size of the silicon particles and controlling the particle size of the silicon carbide particles to be larger than the particle sizes of the silicon particles and the graphite particles, the various features interact with each other, so that the repair layer formed by the composite slurry has better bonding strength with the coated carbon-ceramic brake disc, higher consistency, and higher density of the repair layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of carbon-ceramic brake discs, and in particular to a composite slurry and a preparation method and application thereof. Background Art

[0002] At present, automobile brake discs are still mainly powder metallurgy brake discs and gray cast iron brake discs. This material is heavy, has a low melting point, and is easy to deform. Mid-to-high-end cars and competitive vehicles generally begin to use brake discs made of carbon / ceramic composite materials. This type of brake disc has the advantages of low density, high temperature resistance, high strength, good friction performance and long service life. Carbon / ceramic composite materials mainly contain carbon, silicon and silicon carbide. The carbon is mainly composed of carbon fiber and matrix carbon. These two carbon components can remain stable at room temperature, but are easily oxidized at temperatures above 400°C; when exposed to high temperatures for a long time, brake discs made of carbon / ceramic composite materials may have grooves or other damage on the surface due to oxidation. In order to better prevent carbon oxidation, a coated carbon-ceramic brake disc has been developed. A layer of silicon carbide (SiC) coating is attached to the surface of the brake disc, which can not only improve oxidation resistance, but also enhance its friction performance. At present, the production cost and price of coated carbon-ceramic brake discs on the market are relatively high. If the coated surface of the carbon / ceramic brake disc is directly scrapped due to damage, it will cause great losses. It is necessary to use a repair agent to repair it. However, the coating repaired by traditional repair agents has poor bonding with the coated carbon-ceramic brake disc body.

[0003] Therefore, it is necessary to improve the traditional technology. Summary of the invention

[0004] Based on this, the present application provides a composite slurry having good bonding strength with a coated carbon-ceramic brake disc body, and a preparation method and application thereof.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] On the one hand, the present application provides a composite slurry, whose components, measured by mass percentage, include 5%~10% silicon particles, 55%~65% silicon carbide particles, 5%~10% graphite particles and 25%~35% resin solution, the D50 particle size of the silicon particles is 38 μm~80 μm, the D50 particle size of the silicon particles is smaller than the D50 particle size of the silicon carbide particles, and the D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon carbide particles.

[0007] In some of the embodiments, in the composite slurry, the D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon particles.

[0008] In some of the embodiments, in the composite slurry, the ratio of the D50 particle size of the silicon particles to the D50 particle size of the silicon carbide particles is 0.3-0.96:1.

[0009] In some of the embodiments, in the composite slurry, the ratio of the D50 particle size of the graphite particles to the D50 particle size of the silicon carbide particles is 0.05-0.5:1.

[0010] In some of the embodiments, in the composite slurry, the D50 particle size of the silicon carbide particles is 40 μm to 150 μm.

[0011] In some of the embodiments, in the composite slurry, the D50 particle size of the graphite particles is 10 μm to 20 μm.

[0012] In some of the embodiments, in the composite slurry, the surface of the silicon carbide particles is loaded with the silicon particles and the graphite particles.

[0013] In some of the embodiments, in the composite slurry, the mass ratio of the graphite particles to the silicon carbide particles is 1:10-13.

[0014] In some of the embodiments, in the composite slurry, the solid content of the resin solution is 70% to 80%.

[0015] In some embodiments, in the composite slurry, the resin solution includes a phenolic resin solution.

[0016] On the one hand, the present application provides a method for preparing a composite slurry, comprising the following steps:

[0017] Providing raw materials according to the above composite slurry;

[0018] The silicon particles, the silicon carbide particles, the graphite particles and the resin solution are mixed to prepare a composite slurry.

[0019] On the one hand, the present application provides the use of the above-mentioned composite slurry in repairing coated carbon-ceramic brake discs.

[0020] In some embodiments, the application of the repair coating in the carbon-ceramic brake disc includes the following steps:

[0021] The composite slurry is placed on the to-be-repaired portion of the coated carbon-ceramic brake disc body to form a repair layer, thereby obtaining a coated carbon-ceramic brake disc provided with a repair layer;

[0022] The coated carbon ceramic brake disc provided with a repair layer is melt-siliconized.

[0023] In some embodiments, in the application of repairing coated carbon-ceramic brake discs, the melt siliconizing comprises the following steps:

[0024] The coated carbon ceramic brake disc with the repair layer is placed in a siliconizing furnace, silicon powder is added, and the silicon powder is melted and infiltrated by capillary force to connect the coated carbon ceramic brake disc body with the repair layer.

[0025] In some of the embodiments, in the application of repairing coated carbon-ceramic brake discs, before the step of placing the composite slurry on the area to be repaired of the coated carbon-ceramic brake disc body, the step also includes the steps of successively cleaning and drying the area to be repaired of the coated carbon-ceramic brake disc body.

[0026] In some of the embodiments, in the application of repairing coated carbon-ceramic brake discs, after the step of placing the composite slurry on the coated carbon-ceramic brake disc body at the location to be repaired, the step also includes sequentially curing and polishing the composite slurry placed on the coated carbon-ceramic brake disc body at the location to be repaired to form a repair layer.

[0027] In some of the embodiments, in the application of repairing coated carbon-ceramic brake discs, after the melt siliconizing step, a step of surface treating the coated carbon-ceramic brake disc obtained by the melt siliconizing is also included.

[0028] Compared with the prior art, the composite slurry of the present application has the following beneficial effects:

[0029] The composite slurry of the present application includes graphite particles, silicon particles, graphite particles and resin solution in specific proportions. By controlling the particle size of the silicon particles and controlling the particle size of the silicon carbide particles to be larger than the particle sizes of the silicon particles and the graphite particles, the various characteristics interact with each other, so that the repair layer formed by the composite slurry has better bonding strength with the coated carbon-ceramic brake disc, higher consistency, and higher density of the repair layer. DETAILED DESCRIPTION

[0030] The present application will be further described in detail below in conjunction with the embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0031] It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent forms obtained also fall within the scope of protection of the present application. For example, the features illustrated or described as part of one embodiment can be combined in another embodiment in a suitable manner to produce a new embodiment. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing implementation modes and embodiments and are not intended to limit this application.

[0033] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0034] In the present application, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0035] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.

[0036] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0037] Herein, "preferred", "better", "more preferred", and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0038] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0039] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0040] In the present application, the terms "first", "second", "third", "fourth", etc. in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0041] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0042] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0043] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0044] In this application, the term "room temperature" or "normal temperature" generally refers to 4°C to 35°C, for example, 20°C ± 5°C. In some embodiments of this application, "room temperature" or "normal temperature" refers to 10°C to 30°C. In some embodiments of this application, "room temperature" or "normal temperature" refers to 20°C to 30°C.

[0045] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 3~5 h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).

[0046] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the invention purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0047] The mass or weight of the relevant components mentioned in the specification of the embodiments of the present application may not only refer to the specific content of each component, but also indicate the proportional relationship of the mass or weight between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the specification of the embodiments of the present application, it is within the scope disclosed in the specification of the embodiments of the present application. Specifically, the mass or weight described in the specification of the embodiments of the present application may be units known in the chemical industry such as μg, mg, g, and kg.

[0048] The repair process for non-coated carbon-ceramic brake discs uses carbon fiber cloth as a carrier and is repaired by resin bonding, impregnation, carbonization, and siliconization. This production process has a long production cycle, cumbersome operations, and high repair costs. The defects of these repair parts are mainly caused by carbon fiber cloth as a filler, which is easily oxidized at temperatures above 400°C. During normal braking, the temperature of the brake disc will be above 400°C, and the service life is short.

[0049] An embodiment of the present application provides a composite slurry, whose components include 5% to 10% silicon particles, 55% to 65% silicon carbide particles, 5% to 10% graphite particles and 25% to 35% resin solution, the D50 particle size of the silicon particles is 38 μm to 80 μm, the D50 particle size of the silicon particles is smaller than the D50 particle size of the silicon carbide particles, and the D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon carbide particles.

[0050] The composite slurry of the present application includes graphite particles, silicon particles, graphite particles and resin solution in specific proportions. By controlling the particle size of the silicon particles and controlling the particle size of the silicon carbide particles to be larger than the particle sizes of the silicon particles and the graphite particles, the various characteristics interact with each other, so that the repair layer formed by the composite slurry has better bonding strength with the coated carbon-ceramic brake disc, higher consistency, and higher density of the repair layer.

[0051] Among them, the shrinkage rate of the reaction between graphite and silicon is relatively small, which effectively improves the bonding strength between the repair layer formed by the composite slurry and the coated carbon-ceramic brake disc, and effectively promotes the density of the repair layer; by controlling the particle size of the silicon particles, the holes formed when they melt are relatively small, which effectively improves the consistency of the repair layer and the coated carbon-ceramic brake disc body coating, and effectively improves the density of the repair layer.

[0052] The study found that if the graphite particles are replaced with carbon particles, there will be a gap between the repair layer formed by the composite slurry and the coating of the coated carbon ceramic brake disc, which will lead to a lower bonding force between the repair layer and the coated carbon ceramic brake disc, thus affecting the qualified rate of the repair. The analysis believes that the shrinkage rate of the carbon particles and silicon particles is large.

[0053] If the silicon particles are too large, the bonding force between the repair layer and the coated carbon ceramic brake disc will also weaken. Analysis shows that the silicon particles will melt into liquid during the molten siliconization stage, and large silicon particles will form large holes in the area, which cannot be dense, resulting in pores on the coating surface, causing the bonding force between the repair layer and the coated carbon ceramic brake disc to weaken.

[0054] It can be understood that in the composite slurry, the mass percentage of silicon particles, calculated by mass percentage, includes but is not limited to 5%, 6%, 7%, 8%, 9%, and 10%; the mass percentage of silicon carbide particles includes but is not limited to 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, and 75%; the mass percentage of graphite particles includes but is not limited to 5%, 6%, 7%, 8%, 9%, and 10%; the mass percentage of resin solution includes but is not limited to 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, and 35%.

[0055] It can be understood that in the composite slurry, the mass ratio of silicon particles to silicon carbide particles is 1:5.5 to 1:13. Further, the mass ratio of silicon particles to silicon carbide particles includes but is not limited to 1:5.5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, and 1:13.

[0056] It can be understood that in the composite slurry, the mass ratio of graphite particles to silicon carbide particles is 1:5.5 to 1:13. Further, the mass ratio of graphite particles to silicon carbide particles includes but is not limited to 1:5.5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13. Optionally, the mass ratio of graphite particles to silicon carbide particles is 1:10 to 1:13.

[0057] In some of the examples, in the composite slurry, the D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon particles.

[0058] In some of the examples, in the composite slurry, the ratio between the D50 particle size of the silicon particles and the D50 particle size of the silicon carbide particles is 0.3-0.96:1.

[0059] It can be understood that the ratio between the D50 particle size of the silicon particles and the D50 particle size of the silicon carbide particles includes but is not limited to 0.3:1, 0.38:1, 0.4:1, 0.5:1, 0.53:1, 0.6:1, 0.7:1, 0.76:1, 0.8:1, 0.9:1, and 0.96:1.

[0060] In some of the examples, in the composite slurry, the ratio between the D50 particle size of the graphite particles and the D50 particle size of the silicon carbide particles is 0.05-0.5:1.

[0061] It is understood that the ratio between the D50 particle size of the graphite particles and the D50 particle size of the silicon carbide particles includes, but is not limited to, 0.05:1, 0.06:1, 0.1:1, 0.15:1, 0.2:1, 0.3:1, 0.4:1, and 0.5:1.

[0062] It will be understood that the D50 particle size of the silicon particles includes but is not limited to 38 μm, 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 52 μm, 55 μm, 58 μm, 60 μm, 62 μm, 65 μm, 68 μm, 70 μm, 72 μm, 75 μm, 78 μm, and 80 μm; in some examples, it may be within a range consisting of any two of these point values ​​as end values, the same below.

[0063] In some of these examples, the D50 particle size of the silicon carbide particles in the composite slurry is 40 μm~150 μm.

[0064] It will be appreciated that the D50 particle size of the silicon carbide particles includes, but is not limited to, 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 52 μm, 55 μm, 58 μm, 60 μm, 62 μm, 65 μm, 68 μm, 70 μm, 72 μm, 75 μm, 78 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, and 150 μm.

[0065] In some of these examples, the D50 particle size of graphite particles in the composite slurry is 10 μm~20 μm.

[0066] It is understood that the D50 particle size of the graphite particles includes, but is not limited to, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, and 20 μm.

[0067] In some of these examples, in the composite slurry, the surface of the silicon carbide particles is loaded with particles and graphite particles.

[0068] It can be understood that at least part of the silicon particles and graphite particles are supported on the surface of the silicon carbide particles; it can be further understood that part or all of the silicon particles and graphite particles are supported on the surface of the silicon carbide particles.

[0069] By controlling the particle sizes of silicon particles, silicon carbide particles and graphite particles, the particle sizes of the three particles are slightly different and the mixing uniformity is better, which can further improve the bonding strength and consistency between the repair layer formed by the composite slurry and the coated carbon-ceramic brake disc body as well as the density of the repair layer.

[0070] In some of these examples, the solid content of the resin solution in the composite slurry is 70%~80%.

[0071] Compared with directly using resin as a binder, which requires pressing at a higher temperature and a certain pressure, there is a risk of damage to the coated carbon-ceramic brake disc, which may destroy its main coating and internal fiber structure and reduce its mechanical properties; the present application adopts the form of a resin solution and controls the solid content of the resin solution, which can effectively improve the bonding strength between the repair layer formed by the composite slurry and the coated carbon-ceramic brake disc, without the need for external pressure and non-destructive repair; and the resin carbon formed by the carbonization of the polymer resin reacts with silicon to further enhance the bonding strength between the repair layer and the coated carbon-ceramic brake disc.

[0072] It will be appreciated that the solid content of the resin solution includes, but is not limited to, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, and 80%.

[0073] In some of the examples, in the composite slurry, the resin solution includes a phenolic resin solution.

[0074] It is understood that the phenolic resin solution can be cured at room temperature.

[0075] An embodiment of the present application provides a method for preparing a composite slurry, comprising the following steps:

[0076] Providing raw materials according to the above composite slurry;

[0077] Silicon particles, silicon carbide particles, graphite particles and resin solution are mixed to prepare a composite slurry.

[0078] The shrinkage rate of the reaction between graphite particles and silicon is relatively small, which effectively improves the bonding strength between the repair layer formed by the composite slurry and the coated carbon-ceramic brake disc, and effectively promotes the density of the repair layer; by controlling the particle size of the silicon particles, the holes formed when they melt are relatively small, which effectively improves the consistency between the repair layer and the coating of the coated carbon-ceramic brake disc body, and effectively improves the density of the repair layer; by controlling the particle size of the silicon carbide particles to be larger than the particle size of the silicon particles and the graphite particles, the surface of the silicon carbide particles is loaded with silicon particles and graphite particles, which is beneficial to the subsequent siliconization reaction, thereby improving the bonding strength and consistency between the repair layer and the coating of the coated carbon-ceramic brake disc body and the density of the repair layer.

[0079] In some of the examples, in the method for preparing the composite slurry, silicon particles, silicon carbide particles, graphite particles and a resin solution are mixed and stirred; further, the stirring equipment is a high-pressure pneumatic stirring device; further, the stirring time is 2 h to 3 h.

[0080] One embodiment of the present application provides the use of the above-mentioned composite slurry or the composite slurry prepared by the above-mentioned preparation method in repairing coated carbon-ceramic brake discs.

[0081] In some of these examples, the application of repairing coated carbon-ceramic brake discs includes the following steps:

[0082] The composite slurry or the composite slurry obtained by the preparation method is placed on the part to be repaired of the coated carbon-ceramic brake disc body to form a repair layer, thereby obtaining a coated carbon-ceramic brake disc provided with a repair layer;

[0083] A coated carbon-ceramic brake disc provided with a repair layer is melt-siliconized.

[0084] It can be understood that another embodiment of the present application provides a method for repairing a coated carbon-ceramic brake disc, comprising the following steps:

[0085] The composite slurry or the composite slurry obtained by the preparation method is placed on the part to be repaired of the coated carbon-ceramic brake disc body to form a repair layer, thereby obtaining a coated carbon-ceramic brake disc provided with a repair layer;

[0086] A coated carbon-ceramic brake disc provided with a repair layer is melt-siliconized.

[0087] In some examples, melt siliconizing in applications such as repairing coated carbon-ceramic brake discs involves the following steps:

[0088] A coated carbon-ceramic brake disc with a repair layer is placed in a siliconizing furnace, silicon powder is added, and the silicon powder is melted and infiltrated by capillary force to connect the coated carbon-ceramic brake disc body with the repair layer.

[0089] In some of these examples, the D50 particle size of silica powder is 6 mm to 10 mm in the application of repairing coated carbon ceramic brake discs.

[0090] In some of these examples, in applications for repairing coated carbon-ceramic brake discs, the temperature of molten siliconization is 1450°C~1500°C, the time is 2 h~3 h, and the vacuum degree is less than 1 kPa.

[0091] It can be understood that after the step of placing the silicon powder and before the step of melting and infiltrating the silicon powder by capillary force, the step of evacuating and heating the siliconizing furnace is also included.

[0092] It can be understood that the carbon-ceramic brake disc provided with a repair layer is placed in the siliconizing furnace step, the carbon-ceramic brake disc provided with a repair layer is first placed in a graphite tooling, and then the tooling is placed in the siliconizing furnace.

[0093] Graphite tooling is used to prevent silicon absorption.

[0094] In some of the examples, in the application of repairing coated carbon-ceramic brake discs, before the step of placing the composite slurry on the to-be-repaired portion of the coated carbon-ceramic brake disc body, the step also includes sequentially cleaning and drying the to-be-repaired portion of the coated carbon-ceramic brake disc body.

[0095] Clean impurities from the area to be repaired to improve the bonding strength and performance after repair.

[0096] In some of these examples, ultrasonic cleaning is used in applications for repairing coated carbon-ceramic brake discs. Furthermore, the cleaning frequency is 50 kHz and the cleaning time is 20 min to 30 min.

[0097] In some of the examples, in the application of repairing coated carbon ceramic brake discs, drying is performed in a constant temperature drying oven. Furthermore, the drying temperature is 120℃~130℃ and the drying time is 2h~3h.

[0098] In some of the examples, in the application of repairing coated carbon-ceramic brake discs, after the step of placing the composite slurry on the coated carbon-ceramic brake disc body at the location to be repaired, the step also includes sequentially curing and polishing the composite slurry placed on the coated carbon-ceramic brake disc body at the location to be repaired to form a repair layer.

[0099] It can be understood that when the phenolic resin solution is used as a binder, it can be cured at room temperature; further, the curing time is 6h~8h.

[0100] In some of the examples, in the application of repairing coated carbon-ceramic brake discs, after the melt siliconizing step, a step of surface treating the coated carbon-ceramic brake discs obtained by melt siliconizing is also included.

[0101] It is understood that in some of these examples, the application of repairing coated carbon-ceramic brake discs includes the following steps:

[0102] Step S1: Cleaning and drying the to-be-repaired part of the coated carbon-ceramic brake disc body in sequence;

[0103] Step S2: the composite slurry or the composite slurry prepared by the preparation method is applied to the to-be-repaired portion of the coated carbon-ceramic brake disc body after drying in step S1, and the composite slurry applied to the to-be-repaired portion of the coated carbon-ceramic brake disc body is sequentially cured and polished to form a repair layer, thereby obtaining a coated carbon-ceramic brake disc provided with a repair layer;

[0104] Step S3: melt-siliconizing the coated carbon-ceramic brake disc with a repair layer obtained in step S2;

[0105] Step S4: performing surface treatment on the coated carbon ceramic brake disc obtained by melt siliconization in step S3.

[0106] The above-mentioned composite slurry or the composite slurry prepared by the above-mentioned preparation method is used to repair the to-be-repaired part of the coated carbon-ceramic brake disc body. The formed repair layer has strong adhesion with the coated carbon-ceramic brake disc body and good compatibility. The repair is simple, the cycle is short, and the repair is non-destructive. The uniformity of the repair layer is high, the process stability is good, the repair cost is low, the repair yield is high, the strength is high, and the friction and wear performance is excellent.

[0107] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0108] Example 1

[0109] (1) Use ultrasonic water washing to clean the debris on the surface of the carbon ceramic brake disc coating to be repaired, and then dry it; the ultrasonic cleaning time is 20 min, the cleaning frequency is 50 kHz; the drying equipment is a constant temperature drying oven, the temperature is 120℃, and the drying time is 2~3 h;

[0110] (2) Raw silicon powder, silicon carbide powder, graphite powder and resin solution are mixed in a mass percentage of 5%: 65%: 5%: 25%, and a uniform repair agent is obtained after stirring; wherein the resin solution is a phenolic resin solution with a solid content of 80%; in the repair agent, the D50 particle size of the silicon particles is 38 μm, the D50 particle size of the silicon carbide particles is 50 μm, and the D50 particle size of the graphite particles is 20 μm;

[0111] (3) Filling the repair agent into the surface of the carbon-ceramic brake disc coating repair area after cleaning in step (1), and after the repair agent at the repair area is completely cured, sanding the filled area with sandpaper to make it smooth;

[0112] (4) placing the carbon ceramic brake disc treated in step (3) into a graphite tooling, placing silicon particles (particle size 10 mm) at the repaired part, placing the graphite tooling into a high-temperature siliconizing furnace, evacuating the furnace and heating it to perform melt siliconizing; wherein the temperature of the high-temperature siliconizing furnace is 1450°C, the time is 2 h, and the vacuum degree is less than 1 kPa;

[0113] (5) The carbon ceramic brake disc after molten siliconization is finely processed and the surface is treated to obtain a repaired coated carbon ceramic brake disc.

[0114] Example 2

[0115] The method is basically the same as Example 1, except that in the repairing agent of step (2), the mass percentages of raw silicon powder, silicon carbide powder, graphite powder and resin solution are 5%:60%:5%:30%.

[0116] Example 3

[0117] The method is basically the same as Example 1, except that in the repairing agent of step (2), the mass percentages of raw silicon powder, silicon carbide powder, graphite powder and resin solution are 10%: 55%: 5%: 25%.

[0118] Example 4

[0119] The method is basically the same as Example 1, except that in the repairing agent of step (2), the D50 particle size of the silicon particles is 48 μm, the D50 particle size of the silicon carbide particles is 50 μm, and the D50 particle size of the graphite particles is 20 μm.

[0120] Example 5

[0121] The method is basically the same as Example 1, except that in the repairing agent of step (2), the D50 particle size of the silicon particles is 38 μm, the D50 particle size of the silicon carbide particles is 100 μm, and the D50 particle size of the graphite particles is 20 μm.

[0122] Example 6

[0123] The method is basically the same as Example 1, except that in the repairing agent of step (2), the D50 particle size of the silicon particles is 50 μm, the D50 particle size of the silicon carbide particles is 100 μm, and the D50 particle size of the graphite particles is 15 μm.

[0124] Example 7

[0125] The method is basically the same as Example 1, except that in the repairing agent of step (2), the particle size of the silicon particles is 80 μm, the D50 particle size of the silicon carbide particles is 150 μm, and the D50 particle size of the graphite particles is 10 μm.

[0126] Comparative Example 1

[0127] The method is basically the same as Example 1, except that in step (2), the graphite powder in the repair agent is replaced with carbon powder of equal mass, and the D50 particle size of the carbon particles in the prepared repair agent is 20 μm.

[0128] Comparative Example 2

[0129] The method is basically the same as Example 1, except that in the repair agent of step (2), the D50 particle size of the silicon particles is 2 mm.

[0130] Comparative Example 3

[0131] The method is basically the same as Example 1, except that in the repair agent of step (2), the D50 particle size of the silicon carbide particles is 15 μm, the D50 particle size of the silicon particles is larger than the D50 particle size of the silicon carbide particles, and the D50 particle size of the graphite particles is larger than the D50 particle size of the silicon carbide particles.

[0132] Some component parameters of the repair agent used in each embodiment and comparative example are shown in Table 1, wherein "silicon particles: silicon carbide particles" refers to the ratio between the D50 particle size of silicon particles and the D50 particle size of silicon carbide particles, and "graphite particles: silicon carbide particles" refers to the ratio between the D50 particle size of graphite particles and the D50 particle size of silicon carbide particles.

[0133] Table 1

[0134]

[0135] The performance tests were conducted on the coated carbon ceramic brake discs repaired in the embodiments and comparative examples: the shear strength between the coating and the substrate was tested to characterize the bonding strength between the repair coating formed by the repair agent and the coated carbon ceramic brake disc, and the value was the average of five samples (GB / T 28889-2012); the coating density was tested, and the standard deviation of different densities with the same proportion formula was calculated to characterize the consistency of the repair coating; the compactness was characterized by testing the percentage of the density of the repair coating to the theoretical silicon carbide density (silicon carbide density: 3.21). The results are shown in Table 2.

[0136] Table 2

[0137]

[0138] It can be seen from Table 2 that, compared with Comparative Examples 1 to 3, the repair agents prepared in Examples 1 to 7 have better bonding strength, higher consistency and higher density.

[0139] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0140] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A composite slurry, characterized in that: Calculated by mass percentage, its components include 5% to 10% silicon particles, 55% to 65% silicon carbide particles, 5% to 10% graphite particles and 25% to 35% resin solution, the D50 particle size of the silicon particles is 38 μm to 80 μm, the D50 particle size of the silicon particles is smaller than the D50 of the silicon carbide particles, and the D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon carbide particles.

2. The composite slurry according to claim 1, characterized in that The D50 particle size of the graphite particles is smaller than the D50 particle size of the silicon particles.

3. The composite slurry according to claim 1, characterized in that: The composite slurry meets at least one of the following characteristics: (1) The ratio of the D50 particle size of the silicon particles to the D50 particle size of the silicon carbide particles is 0.3-0.96:1; (2) The ratio of the D50 particle size of the graphite particles to the D50 particle size of the silicon carbide particles is 0.05-0.5:

1.

4. The composite slurry according to any one of claims 1 to 3, characterized in that: The composite slurry meets at least one of the following characteristics: (1) The D50 particle size of the silicon carbide particles is 40 μm to 150 μm; (2) The D50 particle size of the graphite particles is 10 μm to 20 μm; (3) The silicon particles and the graphite particles are supported on the surface of the silicon carbide particles.

5. The composite slurry according to any one of claims 1 to 3, characterized in that: The composite slurry meets at least one of the following characteristics: (1) The solid content of the resin solution is 70% to 80%; (2) The resin solution includes a phenolic resin solution; (3) The mass ratio of the graphite particles to the silicon carbide particles is 1:10-13.

6. A method for preparing a composite slurry, characterized in that: The following steps are involved: Providing raw materials according to the composite slurry according to any one of claims 1 to 5; The silicon particles, the silicon carbide particles, the graphite particles and the resin solution are mixed to prepare a composite slurry.

7. Use of the composite slurry as described in any one of claims 1 to 5 in repairing coated carbon-ceramic brake discs.

8. The use according to claim 7, characterized in that The following steps are involved: The composite slurry is placed on the to-be-repaired portion of the coated carbon-ceramic brake disc body to form a repair layer, thereby obtaining a coated carbon-ceramic brake disc provided with a repair layer; The coated carbon ceramic brake disc provided with a repair layer is melt-siliconized.

9. The use according to claim 8, characterized in that The melt siliconizing comprises the following steps: The coated carbon ceramic brake disc with the repair layer is placed in a siliconizing furnace, silicon powder is added, and the silicon powder is melted and infiltrated by capillary force to connect the coated carbon ceramic brake disc body with the repair layer.

10. The use according to any one of claims 8 to 9, characterized in that: The steps satisfy at least one of the following characteristics: (1) before the step of placing the composite slurry on the to-be-repaired portion of the coated carbon-ceramic brake disc body, the step of sequentially cleaning and drying the to-be-repaired portion of the coated carbon-ceramic brake disc body is also included; (2) after the step of applying the composite slurry to the to-be-repaired portion of the coated carbon-ceramic brake disc body, the method further includes the steps of sequentially curing and polishing the composite slurry applied to the to-be-repaired portion of the coated carbon-ceramic brake disc body to form the repair layer; (3) After the melt siliconizing step, the method further includes a step of surface treating the coated carbon ceramic brake disc obtained by the melt siliconizing.

Citation Information

Patent Citations

  • Carbon-ceramic composite material brake disc and preparation method thereof

    CN110981518A

  • Diamond-silicon carbide composite ceramic and preparation method thereof

    CN114133271A